Lead soaps in paintings: Friends or foes?. (2nd January 2017) - Cotte, Marine; Checroun, Emilie; De Nolf, Wout; Taniguchi, Yoko; De Viguerie, Laurence; Burghammer, Manfred; Walter, Philippe; Rivard, Camille; Salomé, Murielle; Janssens, Koen; Susini, Jean
Abstract : The origin(s) and role(s) of metal soaps in paints are a worldwide concern today. These hybrid compounds, containing both fatty acid chains and metals associated with a carboxylate function, are increasingly identified in paints. As reviewed in the first part of this work, the presence of metal soaps in paints is differently interpreted in scientific publications: metal soaps are sometimes considered to play a positive role as anchor points, during paint drying processes; they can also be considered as responsible for many degradation processes (protrusions, efflorescences, darkening, etc.). Their origins are also interpreted in various ways. In some paintings (in particular from the twentieth century), they have sometimes introduced on purpose, as additives, to modify the physical properties of the painting materials. In older paintings, metal soaps are usually thought to result from an uncontrolled reaction of oil with lead-based pigments, in particular lead white, red lead, and lead tin yellow. In the second part of this work, the review of historical recipes of lead-based paint shows an important number of recipes based on controlled mixing of oil with lead driers. In the third part, the experimental reproduction of such traditional recipes using walnut oil and litharge (PbO) shows that lead soaps can be formed, both in about one hour at ∼100°C, or in about one month at room temperature. It shows as well that after a few years, litharge is no longer detected in the paint medium, while different lead carbonates are. Finally, the micro-infrared spectroscopy and micro-X-ray diffraction re-analysis of protrusions from a nine-year model painting shows together with lead soaps, the presence of Pb5 (CO3 )3 (OH)2 O ('synthetic plumbonacrite'), an unusual phase recently observed in a protrusion from a painting by Vincent Van Gogh. This work highlights (i) the multiple origins and roles of metal soaps in paints and (ii) the importance of combining the analysis of fragments from historical paintings with the analysis and reproduction of historical recipes. In particular, we show that the components detected today in historical paintings may severely differ from those originally used or prepared by the painter, complicating the assessment of the painter's intentions. More than the presence of metal soaps, the key questions to be tackled should be about their origins and (re)mobilization.